Examining Implicit Attitudes towards Exercisers with a Physical Disability. (4th April 2013) - Dionne, Cassandra D.; Gainforth, Heather L.; O'Malley, Deborah A.; Latimer-Cheung, Amy E.
Abstract : Background. Using measures of explicit attitudes, physical activity status has been established as a factor that reduces the stigma able-bodied people hold towards people with physical disabilities. This phenomenon is called the exerciser stereotype. However, whether the exerciser stereotype exists when using measures of implicit attitudes remains unknown. Objective. The aims of this study were to evaluate the prevalence of negative implicit attitudes towards people with physical disabilities and determine whether implicit attitudes towards people with physical disabilities were influenced by the exerciser stereotype. Methods. One hundred able-bodied participants (82 females, 18 males) completed two implicit association tests (IATs): the Disability-Attitudes IAT and the Disability-Activity IAT. The Disability-Attitudes IAT measured implicit attitudes towards people who were not disabled relative to disabled; the Disability-Activity IAT measured attitudes towards people with a physical disability who were active relative to inactive. Results. Results revealed that 83.8% of participants had negative implicit attitudes towards people with a disability. Participants held more positive attitudes towards active versus inactive people with a physical disability. Conclusions. The study findings indicate that the exerciser stereotype exists implicitly and may undermine negative attitudes towards people with physical disabilities.